Book Review of "Cultural Variations in Psychopathology: From Research to Practice" - Barlow, Constance A. (Canadian Journal of Counselling and Psychotherapy, 2013)
This is an edited book that aims to enhance understanding about the intersection of migration, culture, and psychopathology. The book presents research projects, literature reviews, and theoretical frameworks that address cultural variations in psychopathology. This review will provide a summary and critical analysis of the various chapters that address topics related to neuroscience, emotion regulation, diagnosis, and intervention. While the chapters in the book are rich in information and present detailed background literature that is current and relevant, the limitation o fthe book is its underrepresentation of discussions by the authors on how the research findings can be translated into practice.